GRAPHICAL COMPARISON AMONG SITE INDEX CURVES FOR Pinus elliottii AND Pinus taeda, BUILT AT SOUTH BRAZIL - Tonini, Helio (2002)
This research had as main objective to study  the dominant height growth of Pinus elliottii and Pinus taeda through site index curves comparisons in  some regions of Rio Grande do Sul State and other states of the country. These comparisons showed that the site index curves made by Tonini (2000),  for the southeastern mountain  and coast  land in Rio Grande do Sul State did not show the same pattern of those by Scolforo e Machado (1988), for Paraná and Santa Catarina, Brazil (1989a) for  Passo Fundo RS, Marcolin (1990), for the Parana’s Second Upland and Selle (1993) for Cambará do Sul RS. However, the same growth  pattern was observed for curves  by Brasil (1989b) for São Francisco de Paula which only level differences were observed.